1999
DOI: 10.1038/sj.bjc.6690284
|View full text |Cite
|
Sign up to set email alerts
|

Audiotapes and letters to patients: the practice and views of oncologists, surgeons and general practitioners

Abstract: Summary A range of measures have been proposed to enhance the provision of information to cancer patients and randomized controlled trials have demonstrated their impact on patient satisfaction and recall. The current study explored the practice and views of oncologists, surgeons and general practitioners (GPs) with regards to providing patients with consultation audiotapes and summary letters. In stage 1, 28 semi-structured interviews with doctors were conducted to provide qualitative data on which to base a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…At odds are the practitioner's duty to truth telling and the patient's cognitive and emotional appraisal of bad news. Techniques for delivery of bad news are well documented in oncology (Sell et al, 1993;Girgis and Sanson-Fisher, 1995), but studies also recognise that information can be misunderstood or forgotten (Ptacek and Eberhardt, 1996;McConnell et al, 1999;Schofield et al, 2001). The use of audiotapes in medical consultations is a logical antidote to misunderstanding (Hogbin and Fallowfield, 1989;Damian and Tattersall, 1991;Deutsch, 1992;Dunn et al, 1993;McHugh et al, 1995) but, for patients with a poor prognosis, bad news can increase psychological distress (McHugh et al, 1995) and the potential for maladaptive responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At odds are the practitioner's duty to truth telling and the patient's cognitive and emotional appraisal of bad news. Techniques for delivery of bad news are well documented in oncology (Sell et al, 1993;Girgis and Sanson-Fisher, 1995), but studies also recognise that information can be misunderstood or forgotten (Ptacek and Eberhardt, 1996;McConnell et al, 1999;Schofield et al, 2001). The use of audiotapes in medical consultations is a logical antidote to misunderstanding (Hogbin and Fallowfield, 1989;Damian and Tattersall, 1991;Deutsch, 1992;Dunn et al, 1993;McHugh et al, 1995) but, for patients with a poor prognosis, bad news can increase psychological distress (McHugh et al, 1995) and the potential for maladaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has placed a considerable emphasis on effective communication of bad news (Fallowfield, 1993;Sell et al, 1993;Ptacek and Eberhardt, 1996) and numerous approaches have been recommended to evaluate and improve communication (Fallowfield, 1993;McConnell et al, 1999;Schofield et al, 2001). Yet relatively little attention has been paid as to what patients believe about what they are told and how they respond to bad news.…”
mentioning
confidence: 99%
“…It is regrettable that surveys of Australian doctors' views on providing consultation audio-tapes have revealed a marked lack of enthusiasm [14]. If cancer patients and their consumer organisations are enthusiastic, I believe a publicity campaign would be likely to lead to more rapid provision of audio-tape facilities in cancer centres and consulting rooms.…”
Section: Consultation Audio-tapes As An Information Aid For Cancer Pamentioning
confidence: 99%
“…Audio-tapes of oncology consultations have proved acceptable both to patients and to some doctors [14]. Patients receiving such audio-tapes report that they are useful both to themselves and to their families, report higher satisfaction with their medical communication, and in some studies demonstrate improved recall of facts presented during consultations.…”
mentioning
confidence: 96%
“…It has been suggested that letters should be dictated in front of patients [27], with patients reportedly appreciating this sense of openness [50]. In the field of cancer care it has been reported that audiotapes, either instead of or as well as copy correspondence can be helpful in some consultations [51]. Two studies describe the practice of writing separate letters to another health worker and to the patient [18,40].…”
Section: Content and Processmentioning
confidence: 99%